Patterns of respiratory illness in the first year of life. Issue 6550 (27th September 1986) - Watkins, C J; Sittampalam, Y; Morrell, D C; Leeder, S R; Tritton, E
Abstract : This paper describes a study of respiratory illness during the first year of life in a cohort of infants who were born between 1975 and 1978 to mothers who were registered with two inner London group general practices. The types of respiratory illness and their relation to the season of the year and season of birth of the child are examined. The relations among the frequency and type of respiratory illness and several social and family factors that have previously been shown to be associated with high levels of respiratory morbidity are also described.